Polar molecules catalyze CO insertion into metal-alkyl bonds through the displacement of an agostic C-H bond - Zhou, Tian; Malakar, Santanu; Webb, Steven L.; Krogh-Jespersen, Karsten; Goldman, Alan S. (Proceedings of the National Academy of Sciences - PNAS, 2019)
The insertion of CO into metal-alkyl bonds is the key C-C bond-forming step in many of the most important organic reactions catalyzed by transition metal complexes. Polar organic molecules (e.g., tetrahydrofuran) have long been known to promote CO insertion reactions, but the mechanism of their action has been the subject of unresolved speculation for over five decades. Comprehensive computational studies [density functional theory (DFT)] on the prototypical system Mn(CO)₅(arylmethyl) reveal that the polar molecules do not promote the actual alkyl migration step. Instead, CO insertion (i.e. alkyl migration) occurs rapidly and reversibly to give an acyl complex with a sigma-bound (agostic) C-H bond that is not easily displaced by typical ligands (e.g. phosphines or CO). The agostic C-H bond is displaced much more readily, however, by the polar promoter molecules, even though such species bind only weakly to the metal center and are themselves then easily displaced; the facile kinetics of this process are attributable to a hydrogen bonding-like interaction between the agostic C-H bond and the polar promoter. The role of the promoter is to thereby catalyze isomerization of the agostic product of CO insertion to give an η²-C,O-bound acyl product that is more easily trapped than the agostic species. This ability of such promoters to displace a strongly sigma-bound C-H bond and to subsequently undergo facile displacement themselves is without reported precedent, and could have implications for catalytic reactions beyond carbonylation.